Immersivity: An Interdisciplinary Approach to Spaces of Immersion - Florian Freitag; Céline Molter; Laura Katharina Mücke; Helena Rapp; Damien B. Schlarb; Elisabeth Sommerlad; Clemens Spahr; Dominic Zerhoch (Ambiances)
This article proposes to shift the scholarly focus from the conceptually, terminologically, and methodologically fuzzy notion of “immersion” to the concept of “immersivity,” and thus from a discussion of experiences to an analysis of the productive forces that enable such experiences (aesthetic and otherwise). Using case studies from theme parks, film, and immersive theatre to video games and immersive educational spaces, we argue that immersivity is a distinct term that denotes an inherent quality of objects in general and of mediated, delineated, real and virtual spaces in particular. We assume that in all of these examples, spatial qualities and modes interact in particular ways to facilitate immersion. Elucidating these interactions requires discussing examples from different disciplinary contexts. It is precisely through this interdisciplinary approach that we take a first step towards understanding immersivity, as we pinpoint cross-disciplinary congruences wherever possible. The article thus offers the starting point for a transdisciplinary, qualitative, experimental, and analytical model of immersivity. Following a theoretical introduction to the topic of immersion, we will first conceptualize our interdisciplinary understanding of immersion and immersivity and then launch into a transdisciplinary dialogue about examples of immersive spaces.